What went wrong? case histories of process plant disasters - Kletz, Trevor A. (Houston, Tex. : Gulf Pub., 1998)
Expert Trevor Kletz examines the causes and aftermaths of numerous plant disasters--almost every one of which could have been prevented. Case histories illustrate what went wrong, why it went wrong, and then guide you in how to circumvent similar tragedies. Learn from the mistakes of others. This invaluable and respected book examines the causes and aftermaths of numerous plant disasters - almost every one of which could have been prevented. Case histories illustrate what went wrong and why it went wrong, and then guide you in how to circumvent similar tragedies. * Learn from the mistakes of others with this important book! * Examines the causes and aftermaths of numerous plant disasters - most of which could have been prevented * Case histories illustrate what went wrong, why it went wrong, and then guide you in how to circumvent similar tragedies.
Acknowledgments. Preface. Units and nomenclature. Preparation for maintenance. Modifications. Accidents caused by human error. Labeling. Storage tanks. Stacks. Leaks. Liquefied flammable gases. Pipe and vessel failures. Other equipment. Entry to vessels. Hazards of common materials. Tank trucks and cars. Testing of trips and other protective systems. Static electricity. Materials of construction. Operating methods. Reverse flow and other unforeseen deviations. I didn't know that. Problems with computer control. Inherently safer design. Reactions-planned and unplanned. A final word. Recommended reading. Index.
Includes bibliographical references and index.
Keywords: Chemical plants -- Accidents; Electronic books